Interrogating the Shortcomings of the New Alliance for Food Security and Nutrition from a Human Rights Perspective - Kibungu, Joseph (University of the Witwatersrand, Johannesburg, 2023)
Access to food entails the physical means to obtain food directly, and economic access, which is the ability to purchase food from available sources. Lack of access to food continues to deny a significant proportion of the globe, especially women and peasant farmers, a dignified life. There have been many attempts at both local and international levels to address food insecurity in Sub-Saharan Africa (SSA).2 Most recent attempts have championed agribusinesses to solve food insecurity, with increasing agribusiness involvement from the Global North. The primary advocates of this model have been agribusinesses’ home states and international financial institutions. At face value, the injection of capital by the private sector to boost agricultural production seems like a noble idea. The proponents of this model champion it as the remaining piece in the jigsaw to accelerate food production in developing economies. They view it as the ultimate solution to ongoing food insecurity in a continent with abundant, unutilized arable land
A research report submitted in partial fulfillment of the requirements for the Doctorate of Laws to the Faculty of Commerce, Law and Management, School of A law, University of the Witwatersrand, Johannesburg, 2023
Keywords: Access to food; Food insecurity in Sub-Saharan Africa; Nutrition; Human Rights Perspectiv; Food security; Access to food; UCTD; SDG-2: Zero hunger